Endometrial Cancer Lymphadenectomy Trial (ECLAT) (pelvic and para‐aortic lymphadenectomy in patients with stage I or II endometrial cancer with high risk of recurrence; AGO‐OP.6). Issue 7 (July 2021) - Emons, Günter; Kim, Jae‐Weon; Weide, Karin; de Gregorio, Nikolaus; Wimberger, Pauline; Trillsch, Fabian; Gabriel, Boris; Denschlag, Dominik; Kommoss, Stefan; Aydogdu, Mustafa; Papathemelis, Thomas; Gropp‐Meier, Martina; et al.
ABSTRACT : Background : The impact of comprehensive pelvic and para‐aortic lymphadenectomy on survival in patients with stage I or II endometrial cancer with a high risk of recurrence is not reliably documented. The side effects of this procedure, including lymphedema and lymph cysts, are evident. Primary Objective : Evaluation of the effect of comprehensive pelvic and para‐aortic lymphadenectomy in the absence of bulky nodes on 5 year overall survival of patients with endometrial cancer (International Federation of Gynecology and Obstetrics (FIGO) stages I and II) and a high risk of recurrence. Study Hypothesis : Comprehensive pelvic and para‐aortic lymphadenectomy will increase 5 year overall survival from 75% (no lymphadenectomy) to 83%, corresponding to a hazard ratio of 0.65. Trial Design : Open label, randomized, controlled trial. In arm A, a total hysterectomy plus bilateral salpingo‐oophorectomy is performed. In arm B, in addition, a systematic pelvic and para‐aortic lymphadenectomy up to the level of the left renal vein is performed. For all patients, vaginal brachytherapy and adjuvant chemotherapy (carboplatin/paclitaxel) are recommended. Major Inclusion Criteria : Patients with histologically confirmed endometrial cancer stages pT1b‐pT2, all histological subtypes, and pT1a endometrioid G3, serous, clear cell, or carcinosarcomas can be included when bulky nodes are absent. When hysterectomy has already been performed (eg, for presumed low risk endometrial cancer), study participation is also possible. Exclusion Criteria : Patients with pT1a, G1 or 2 of type 1 histology or uterine sarcomas (except for carcinosarcomas), endometrial cancers of FIGO stage III or IV (except for microscopic lymph node metastases) or visual extrauterine disease. Primary Endpoint : Overall survival calculated from the date of randomization until death. Sample Size : 640 patients will be enrolled in the study. Estimated Dates for Completing Accrual and Presenting Results : At present, 252 patients have been recruited. Based on this, accrual should be completed in 2025. Results should be presented in 2031. Trial Registration : NCT03438474.